2021
DOI: 10.1007/s11030-021-10207-5
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and fungicidal activity of 3,4-dichloroisothiazolocoumarin-containing strobilurins

Abstract: Twenty-one novel 3,4-dichloroisothiazolocoumarin-containing strobilurins were rationally designed and synthesized. Preliminary bioassay showed that compounds 7c, 7h and 7l exhibited over 80% inhibitory rate against Sclerotinia sclerotiorum at 50 μg/mL, 7c exhibited good activity against S. sclerotiorum with median effective concentration (EC 50 ) of 4.08 μg/mL, while the positive control coumoxystrobin showed EC 50 of 1.00 μg/mL. In addition, 7d showed better fungicidal activity with a lower EC 50 value of 7.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A series of 21 novel 3,4-dichloroisothiazolocoumarin-containing strobilurins were rationally designed and synthesized by Fan and co-workers ( Lv et al, 2022 ). Derivative 189 exhibited good antifungal activity against Sclerotinia sclerotiorum with a EC 50 of 4.08 µM, (coumoxystrobin was used as reference, EC 50 = 1.0 µM) ( Figure 2B ).…”
Section: Biological Applications Of Coumarin Derivativesmentioning
confidence: 99%
“…A series of 21 novel 3,4-dichloroisothiazolocoumarin-containing strobilurins were rationally designed and synthesized by Fan and co-workers ( Lv et al, 2022 ). Derivative 189 exhibited good antifungal activity against Sclerotinia sclerotiorum with a EC 50 of 4.08 µM, (coumoxystrobin was used as reference, EC 50 = 1.0 µM) ( Figure 2B ).…”
Section: Biological Applications Of Coumarin Derivativesmentioning
confidence: 99%
“…The lead compound 40a exhibited remarkable in vitro fungicidal activity against S. sclerotiorum (EC 50 = 4.08 μg/mL), close to that of control coumoxystrobin (EC 50 = 1.00 μg/mL). Another lead compound 40b showed good in vitro fungicidal activity against B. cinerea with EC 50 value of 17.65 μg/mL, slightly better than that of trifloxystrobin (EC 50 = 21.96 μg/mL) …”
Section: β-Methoxyacrylate Derivatives As Pesticidesmentioning
confidence: 99%
“…Another lead compound 40b showed good in vitro fungicidal activity against B. cinerea with EC 50 value of 17.65 μg/mL, slightly better than that of trifloxystrobin (EC 50 = 21.96 μg/ mL). 65 These results demonstrated that coumarin could serve as a promising side chain for novel β-methoxyacrylate pesticide discovery and natural products could be an important source of side chains.…”
Section: β-Methoxyacrylate Derivatives As Pesticidesmentioning
confidence: 99%
“…Agrochemicals are important strategical materials for crop protection and food safety production [ 1 , 2 ]. However, the unreasonable and unscientific use of some pesticides has also resulted in a series of risks [ 3 , 4 ], including increasing pest resistance [ 5 ], toxicity against non-target organisms and potential environmental pollution [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although compounds 1a and 1b displayed favorable in vitro activity, their in vivo performance was suboptimal [ 1 ]. Subsequently, a series of 3,4-dichloroisothiazolocoumarin-containing strobilurins were developed and found to have poor solubility [ 2 ]. To continue the exploration of fungicidal leads and improve the physicochemical properties of a weak acidic moiety of 7-hydroxy group on the coumarins, the esterification of 7-hydroxy coumarins was carried out ( Figure 2 ), the in vitro and in vivo fungicidal activity of the target compounds were simultaneously evaluated, and notably, compounds 2ai and 2ar were found to show good activity.…”
Section: Introductionmentioning
confidence: 99%